DINAMIKA pH TANAH BERPIRIT AKIBAT PERUBAHAN KONDISI AIR DAN APLIKASI AMELIORAN - Marsi, Marsi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2024)
Naturally, during dry season, pyrite tent to be oxidized due to soil water content and groundwater level decrease. This paper aims to evaluate the influence of soil water condition and ameliorants on pyritic soil pH dynamics. Pyritic soil was taken from a depth of 70-90 cm below soil surface in the acid sulphate land located at Mulyasari Village, Tanjung Lago District, Banyuasin Regency, South Sumatra. The research was carried out in greenhouse with 2 treatment factors, namely: Water condition (K1 = water condition maintained at 5 cm above soil surface during incubation period and K2 = water condition at 5 cm above soil surface and allowed to decrease during incubation period) and ameliorant (T = Without Ameliorant, B = Organic Matter, D = Dolomite, P = Phosphate Fertilizer and S = Silicate Coal Ash). The results showed that pyritic soil pH tended to be stable during incubation period for K1 treatment, and pH of soil treated with dolomite > Silicate Coal Ash > Organic Matter > P Fertilizer > Without Ameliorant. Meanwhile for K2 treatment, soil pH tended to decrease with the highest rates are 21.58x10-2, 19.33x10-2, 4.38x10-2, 7.50x10-2, and 12.07x10-2 pH unit per day, respectively for without ameliorant, organic matter, dolomite, phosphate fertilizer and silicate coal ash. The highest rate of decrease in pH of pyritic soil occurred in the range of decreasing water content from 66.31 to 41.73% for without ameliorant, organic matter and phosphate fertilizer, from 41.73 to 13.93% for silicate coal ash, and from 13 .93 to 8.22 % for dolomite. These findings can be applied for managing pyritic soil by maintaining soil water content from falling under water content critical limit range and under uncontrolled dry conditions it is recommended to use lime to minimize pyrite oxidation.